If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -5) = -11 Reorder the terms: 2(-5 + 3x) = -11 (-5 * 2 + 3x * 2) = -11 (-10 + 6x) = -11 Solving -10 + 6x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 6x = -11 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = -11 + 10 6x = -11 + 10 Combine like terms: -11 + 10 = -1 6x = -1 Divide each side by '6'. x = -0.1666666667 Simplifying x = -0.1666666667
| -2=-(2n-8) | | (8x^3-8x^2-26x-10)/(2x-5) | | 69-5x=22x+24 | | 14+3y=17 | | 25=z/-3 | | x*10-18=52 | | -5(m-4)=12 | | ln(x-3)=ln(5x)+ln(2) | | a/7+12=9 | | 7-8x=76-29x | | 3a-9whena=5 | | -4x-40-6=-3x+6 | | -512^1/3 | | 3/5+x=2/3 | | 3(x+6)=10 | | 48a-21-8= | | 5z+3=28 | | -7+9y+5n-4y-3n-29= | | -7x+3=-9x+7 | | x-2/13=9/13 | | 14-5(3x-7)=-26 | | (4ba^2)(a^4b^0)= | | 25-12x=13 | | b-11=-8 | | 3x^2-9x-27=0 | | (8x-3)(x+2)=4 | | 8x+2-6x=1+x-8 | | -35/12=20/3x | | 10y-11=-2 | | 8-8x=20x+19 | | F-12=1 | | 3x-4+6=2x+8 |